A Genetic Structuralism Analysis of Mahmoud Darwish’s Poem “Ahinnu Ila Khubzi Ummi” - Hamdy, Mohammad Zainal; Umniyah, Umniyah (Dzil Majaz: Journal of Arabic Literature, 2025)
Literary works are often created based on an author’s personal experiences or imaginative ideas, which shape the meaning and aesthetic value of the text. However, readers frequently face challenges in understanding the implicit messages conveyed by the author, especially in poetry that combines beauty and depth of meaning. This study aims to analyze Mahmoud Darwish’s poem “Ahinnu Ila Khubzi Ummi” through the lens of genetic structuralism in order to reveal both intrinsic and extrinsic elements that construct its meaning. The research employs a qualitative approach using the library method by collecting and reviewing relevant journals, books, and documents related to genetic structuralism and Darwish’s works. The analysis identifies intrinsic elements such as theme, tone, imagery, and message, which reflect strong emotional and patriotic nuances. Additionally, extrinsic elements, including the author’s social and historical context, reveal the influence of Palestinian identity and resistance on the creation of the poem. The study also notes stylistic features such as repeated words (hyperbole) and certain ambiguous stanzas that require interpretative reading to uncover hidden meanings. The findings demonstrate that the poem is not only an expression of personal longing but also a symbol of national struggle and cultural memory. This research contributes to the field of literary studies by offering an in-depth understanding of how genetic structuralism bridges textual analysis with socio-historical context, particularly in modern Arabic resistance poetry